E-mail@work Get moving with digital communication - Whelan, Jonathan (Harlow : Ft.Com, 2000)
Gives advice on avoiding pitfalls and it includes checklists, flowcharts and case studies
1. introduction -- 2. a closer look at e-mail -- 3. managing your mail -- 4. e-mail and security -- 5. e-mail and the law -- 6. developing a business e-mail policy -- 7. creating good messages.
Includes index.
Keywords: BUSINESS COMMUNICATION